Pengembangan Literasi Membaca dalam Kurikulum Pendidikan Dasar di Kelas IV SDN Ngastemi 1 Kecamatan Bangsal Kabupaten Mojokerto - Zamroji, Muhammad; Indahwati, Nurul (Ats-Tsaqofi: Jurnal Pendidikan dan Manajemen Islam, 2022)
Indonesia is entering the era of the industrial revolution 4.0 which requires its people to be more creative, skilled, and able to solve problems in everyday life. Therefore, it is very necessary for Human Resources who have the ability in the realm of atttudes, knowledge and skills. One of the efforts made through education is the development of reading literacy to became literat citizens, development is carried out on the educational curriculum and starting from elementary school level. The purpose of this study was to describe the development in reading literacy in the core competencies of attitudes, to describe the development of reading literacy in the core cognitive competencies and to describe the development in reading literacy in the core psychomotor competencies. the research method uses qualitative research approach with data collection methods in the form of observation, interviews and documentation. Sources of data used are primary data sources obtained directly from the field or research location, and secondary data sources that support and strengthen research results. Analysis technique with reduction of data collected according t the aspect of the problem so that it becomes data that is ready to be presented and verified and write conclusions. The results of the study indicate that the development of reading literacy can change attitudes in students, foster curiosity so that they are motivated to read in order to gain knowledge and be more creative in their work by following the development of science and technology in this era.